The Tec Kinase Itk Integrates Naïve T Cell Migration and In Vivo Homeostasis - Thelen, Flavian; Wissmann, Stefanie; Ruef, Nora; Stein, Jens V. (Frontiers in Immunology, 2021)
Naïve T cells (TN) constitutively recirculate through secondary lymphatic organs (SLOs), where they scan dendritic cells (DCs) for cognate peptide-loaded major histocompatibility complexes (pMHC). Continuous trafficking between SLOs not only enables rapid clonal selection, but also ensures TN homeostasis by providing access to prosurvival signals from TCR, IL-7R and the chemokine receptor CCR7. Inside lymphoid tissue, CCR7-mediated TN motility is mainly driven by the Rac activator DOCK2, with a separate contribution by a phosphoinositide-3-kinase gamma (PI3Kg)-dependent pathway. Tec tyrosine kinases and the Rac activator Tiam1 constitute prominent downstream effectors of PI3K signaling. Yet, the precise role of Tec kinase versus Tiam1 signaling during CCR7-mediated TN migration and homeostasis remains incompletely understood. Here, we examined the function of the Tec family member interleukin-2-inducible T-cell kinase (Itk) and Tiam1 during TN migration in vitro and in vivo using intravital microscopy. Itk deficiency caused a mild decrease of CCR7-triggered TN migration, mirroring observations made with PI3Kg-/- T cells, while lack Tiam1 did not affect TN motility. In silico modelling suggested that reduced migration in absence of Itk does not result in a substantial decrease on the frequency of TN encounters with DCs within lymphoid tissue. In contrast, Itk was important to maintain in vivo homeostasis of CD4+ TN, also in MHCII-deficient hosts. Taken together, our data suggest that Itk contributes to TN migration and survival by integrating chemokine receptor and TCR signaling pathways.